E-government in latin america: a systematic review (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
Electronic government, or e-government, is the use of technological communication devices, such as computers and the Internet, to provide better public services to serve citizens and thedevelopment of the country as a whole. E-government is not just something related to online procedures or organizational or process restructuring. It is a sociological and political conceptionthat today does not seem to be conceptually present in a clear way. These experience models can serve as a basis for the development of similar solutions in other countries, taking intoaccount the importance of the use of ICTs to increase the efficiency and effectiveness of public functions, facilitate the governmentcitizen relationship and strengthen national strategies to promotetransparency and integrity. The use of technological tools also fosters the development of a knowledge society, which is an essential condition for achieving the social, economic and politicalgoals of countries. In it, governments are committed to identifying ways to use information and communication technologies to promote, in particular, the modernization of the State, and withthem, greater efficiency and transparency in the management and provision of services in the public sector, in order to meet the needs and aspirations of all people. The information related to thecountries has been provided and/or validated by the national authorities in charge of these issues.